Islands of inquiry : colonisation, seafaring and the archaeology of maritime landscapes - Clark, Geoffrey R. (Geoffrey Richard), 1966-; Leach, Foss, 1942-; O'Connor, Sue; Anderson, Atholl (Terra Australis, 2008)
"Many of the papers in this volume present new and innovative research into the processes of maritime colonisation, processes that affect archaeological contexts from islands to continents. Others shift focus from process to the archaeology of maritime places from the Bering to the Torres Straits, providing highly detailed discussions of how living by and with the sea is woven into all elements of human life from subsistence to trade and to ritual. Of equal importance are more abstract discussions of islands as natural places refashioned by human occupation, either through the introduction of new organisms or new systems of production and consumption. These transformation stories gain further texture (and variety) through close examinations of some of the more significant consequences of colonisation and migration, particularly the creation of new cultural identities. A final set of papers explores the ways in which the techniques of archaelogical sciences have provided insights into the fauna of the islands and the human history of such places."--Provided by publisher